An Empirical Analysis of Liquidity, Solvency, Capital Structure and Financial Health of Small and Medium Enterprises in Malaysia - Liew, Zhi Wei; Babak, Naysary (INTI International University, 2021)
Small and Medium Enterprises (SMEs) have been the backbone of Malaysian economy as they are generally deemed as the driving force of economic growth, job creation, and poverty reduction in the country. They have been the means through which accelerated economic growth and rapid industrialization have been achieved. While their contributions to development are generally acknowledged, Small and Medium Enterprises confront many obstacles that limit their short to long-term survival and development. To ensure Small and Medium Enterprises to survive, therefore, the purpose of this study is to carry out a financial diagnosis of Malaysian Small and Medium Enterprises financial performance by focusing on their liquidity, solvency, capital structure, and profitability positions using financial ratio analysis. The financial ratios used in this study are solvency ratio, debt-to-equity ratio, current ratio, return on equity ratio and return on asset ratio. Data for the study covered the period 2015 to 2020 and 100 private limited companies from different sectors registered under the SME Corporation website are selected randomly from the listing of SME100 Awards. Data collected through the analysis of key ratios are analyzed using multiple regression. Then, test and assess the Beta Coefficient followed by Multicollinearity test, with the aim to identify the extend of correlation between independent variables and dependent variables. The outcome of this study would provide some insights to internal and external stakeholders towards designing and implementing future strategies to enhance enterprises financial performance.